Navigating Conditional Press: Negotiating News in Madura, Indonesia - Surokim, Surokim; Ida, Rachmah; Widodo, Suko; Adnan, Hamedi Mohd (Jurnal Kajian Jurnalisme, 2026)
Background: Journalists in Indonesia, and particularly on Madura Island, experience numerous problems when carrying out their professional duties. Despite the official guarantee of press freedom, journalists struggle with numerous obstacles stemming from laws, social and cultural norms, political and economic pressures, and accelerating digital development. Purpose: Investigate the challenges faced by the local journalists on Madura and analyze how these journalists have overcome such challenges and kept their journalistic independence. Methods: The study adopts a qualitative approach using thematic synthesis based on in-depth interviews and data from local journalists on Madura Island. The analysis is conducted on 9 cases of journalists working in print, online, television, and digital media. Results: Journalism in Madura is characterized by the ongoing negotiation with constraints and four kinds of challenges that faced journalists include: the lack of legal protection for local journalists who face threats when reporting issues that are of high sensitivity; dominant local social and cultural power structures; economic and political dependencies; and rapid changes in digital media that require journalistic to adapt in newsroom and in the ways they connect to the audience. Conclusion: Local journalism in Madura operates within structural constraints yet remains flexible, with autonomy that must be renegotiated continually. Sustainability in local journalism depends on improving support for local journalists, securing independent media, and developing new competencies. Local journalism must evolve along with current political and social changes and technological advances. Implications: Local journalists need certain legal protections, greater media independence, and capacity building to respond to the socio-political, economic, and digital contexts in which they work. The quality of their independence at the local level would then depend on journalists' agency to struggle for spaces of autonomy, given these structural limitations.